Polymophisms in ghrl gene in murrah buffaloes (Bubalus bubalis) - Gil, F. M.M. [UNESP]; Souza, F. R.P. [UNESP]; Fonseca, L. F.S. [UNESP]; Tonhati, H. [UNESP] (My University, 2010)
Ghrelin is a gastrointestinal hormone that has action as releasing growth hormone. In cattle, the growth hormone gene is associated with fat percentage, protein, and milk yield. Thus, the ghrelin gene becomes a candidate gene for identification of genetic markers related to milk traits in dairy animals. In this context, the aim of the present study was to identify polymorphisms in the ghrelin gene in buffaloes (Bubalus bubalis). The sample was constituted by 122 Murrah buffaloes from three farms in Sao Paulo state. Was performed PCR-SSCP (Polymerase Chain Reaction - Single Strand Conformation Polymorphism) and DNA sequencing for identification of the polymorphisms. The SSCP technique was able to discriminate three different patterns of migration, known as AA, AB and BB. By sequencing of the three patterns were obtained sequences of 394 bp which were identified 2 SNPs (Single Nucleotide Polymorphisms), confirming the results obtained by SSCP. The SNPs are located in the intron 1 in the positions 138 and 272, constituting the haplotypes GG and AC. Further studies include the characterization of the allele frequencies of these polymorphisms and haplotypes in buffaloes and association studies between these SNPs and milk traits.
Keywords: Buffalo; Ghrelin; Milk production; Molecular markers; SSCP